Enhancing Arabic Grammar Skills and Student Engagement: Analysing the Impact of The Website Arabicmadinah.com in Teaching Arabic Syntax As A Foreign Language: Meningkatkan Penguasaan Tata Bahasa Arab dan Keterlibatan Siswa: Analisis Dampak Website ArabicMadinah.com dalam Pembelajaran Sintaksis Bahasa Arab sebagai Bahasa Asing - Ubaidillah; Fanni Izzatul Millah; Siti Rizqiyah Lestari; Tahir (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2026)
The Madinah Arabic website provides free Arabic language learning materials, including images, instructional videos, and conversational content on YouTube. Although numerous studies have discussed the use of digital media in Arabic language learning, research on the implementation of the Madinah Arabic website for teaching Arabic grammar (nahwu) in Islamic boarding school settings remains limited, particularly in schools with restricted access to digital devices. Therefore, this study aimed to implement the website https://www.madinaharabic.com/ in nahwu instruction at MTs Nahdlatul Ulum Kresek Tangerang and to examine its effectiveness in improving students' grammatical understanding. This study employed a quantitative, quasi-experimental design with a Nonequivalent Control Group Design. Data were collected through observation, pretest-posttest, interviews, and library research. The participants were seventh-grade students at MTs. The findings revealed that the use of web-based media significantly improved students' competence in nahwu. The experimental class showed an increase in mean scores from 41.76 in the pretest to 82.79 in the posttest, while the control class improved from 42.30 to 78.24. The t-test results indicated a p-value of < 0.05, demonstrating that the Madinah Arabic website was effective in helping students understand and apply Arabic grammatical rules. Keywords: Arabic Learning Media, Nahwu Learning, Web-Based Learning